Slow Samson - Christou, Bethany (Somerville, Massachusetts : Templar Books, an imprint of Candlewick Press, 2020)
Everyone likes Samson the sloth, and he gets lots of invitations to parties. The problem is that he's far too slow to ever get there on time. When Samson finally makes it to the celebration, the cake is eaten and the party games are finished. Luckily Samson's resourceful friends have a plan.
Keywords: Sloths -- Juvenile fiction; Animals -- Juvenile fiction; Friendship -- Juvenile fiction; Parties -- Juvenile fiction; Sloths -- Fiction; Animals -- Fiction; Friendship -- Fiction; Parties -- Fiction